The Treatment of Lexical Ambiguity in Machine Translation - عبدالله، توفيق عزيز; ذنون، صفوان ادريس (جامعة الموصل - كلية الآداب, 2019)
يسلط هذا البحث الضوء على واحدة من أصعب المشكلات فيما يخص تصميم برنامج ترجمة لمعالجة الغموض. ويبنى البرنامج على شكل فئات من الكلمات التي لا يمكن أن تكون متجاورة في الجملة. تمتلك آية مفردة من الناحية الدلالية معاني مختلفة بالاعتماد على السياق الذي تقع فيه. ومن المعروف بان الحاسوب ليس لديه القدرة على التفكير كالبشر باعتباره آلة ولهذا فان هدفنا هو إيجاد أفضل وسيلة لتحليل الجملة بطريقة رياضية أي بإيجاد برنامج يستخدم قواعد بيانات وحسابات ووحدات برمجية بحيث يمكن ربطها مع بعضها البعض لمعرفة الغموض. This research sheds light on one of the most difficult problems especially in designing a translation programme which deals with ambiguity. The programme can be built in a form of categories of words that cannot be adjacent in a sentence. From a semantic point of view, a word certainly has different meanings depending on situations and contexts. It is known that a computer as a machine cannot think as a human being. Thus, our aim is to find a best way of analysing a sentence in a mathematical way, i.e. to find out a programme that uses data bases, calculations, modules that can be linked to each other for specifying the lexical ambiguity.
Keywords: التطبيقات اللغوية -- الترجمة الآلية -- الغموض النحوي -- معالجة غموض المفردات